2022
DOI: 10.3390/brainsci12080993
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Post-Stroke Depression: A Retrospective Cohort Study

Abstract: Despite reports of a high incidence and various predictors of post-stroke depression (PSD), the underdiagnosis and undertreatment rates of PSD are still high. This study aimed to examine the incidence of depression in stroke patients and identify factors associated with PSD. This was a retrospective cohort study on ischemic stroke patients from the Geisinger Neuroscience Ischemic Stroke (GNSIS) registry. The following statistical analyses were performed to predict PSD in the studied population: a Kaplan–Meier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Identifying factors associated with PSD is very important due to the underdiagnosis and undertreatment of PSD. At present, various studies indicated that chronic stress (including financial and health-related stress, irrespective of age), [ 48 ] IL-33 concentration of ≤71.85 ng/L [ 49 ] significantly increased the risk for PSD. And Shi YZ et al pointed out that female gender, smoking, mild global cognitive impairment, and stroke recurrence predict early-onset or late-onset PSD after minor ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying factors associated with PSD is very important due to the underdiagnosis and undertreatment of PSD. At present, various studies indicated that chronic stress (including financial and health-related stress, irrespective of age), [ 48 ] IL-33 concentration of ≤71.85 ng/L [ 49 ] significantly increased the risk for PSD. And Shi YZ et al pointed out that female gender, smoking, mild global cognitive impairment, and stroke recurrence predict early-onset or late-onset PSD after minor ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 While the one-third prevalence rate for PSD is well-supported across studies, some studies have reported lower rates ranging from 15.8% to 21%, depending on setting and time since stroke. 18 , 19 Higher rates have also been reported, and the cumulative incidence of PSD may be as high as 55%. 20 The varying rates of depression after stroke are due to combined factors, mostly related to methodology.…”
Section: Post Stroke Depressionmentioning
confidence: 99%
“…Research suggests that marital status, years of education, history of prior stroke and/or history of myocardial infarction, recent life stressors, poverty, and lack of social supports are associated with a higher incidence of depression following a stroke. 18 , 21 , 31 …”
Section: Risk Factorsmentioning
confidence: 99%
“…Previous studies identified several risk factors for PSD. For example, PSD occurs at a greater rate after left-hemispheric stroke [ 7 ], strokes in the frontal lobe or basal ganglia [ 8 ], more anterior location of stroke [ 9 ], more severe stroke [ 3 ], level of physical disability [ 10 ], level of dependence on others [ 11 ], history of previous stroke [ 11 ], chronic accumulation of small macrovascular and microvascular lesions [ 12 ], female gender [ 13 ], treatment for depression prior to stroke [ 10 ], diabetes mellitus [ 14 ], history of myocardial infarction [ 15 ], stressful life events in the months before stroke [ 13 ], living alone at time of stroke [ 16 ], Medicaid patients (versus private insurance patients) [ 15 ], and lower educational attainment [ 16 ]. Comorbidities such as pseudobulbar affect [ 13 ], anxiety [ 3 ], and greater cognitive impairment are more common in patients with PSD [ 17 ].…”
Section: Introductionmentioning
confidence: 99%